A Prototype for Securing Suitcase Travel using RFID and GPS Tracker - Melinda Dwika Nur Setiyawati; Hilal H Nuha; Rahmad Yasirandi (STMIK Budi Darma, 2020)
In recent years, most people use their free time to visit several places, namely traveling. People travel using suitcases and backpacks to keep their luggage. Everyone requires security and comfort when they travel because security is very important for the Traveler. However, losing items often confuse a person since the person must be worried and wants to be able to find the lost items as soon as possible. The security system in this suitcase is also still conventional where people still maintain the contents of the suitcase only by using padlock as security some are already using a combination of numbers but can still lose. As reposted by many Lost and Founds facilities airports, incidents of loss of goods often occur and the found suitcases are broken into using pointy objects. Therefore, to overcome these problems, a system is created to become a solution to secure suitcases. This suitcase security system uses RFID which can open the suitcase lock and use GPS Tracking to find out the coordinates of the suitcase. This system can provide information when the suitcase is opened by force and can also find out the current location of the suitcase to the smartphone